Digital Literacy of Indonesian Teachers on AKM Class and Asesmenpedia - Suhud Aryana; Ida Zulaeha; Rahayu Pristiwati; Haryadi Haryadi (International Conference on Science, Education, and Technology, 2022)
Abstract. Teacher's digital literacy portrait on the application of the AKM kelas and Asesmenpedia it was very important to know because it could be effects of teacher’asessing quality for students learning in the technology era. The research was conducted to Indonesian language teacher. This research used descriptive and predictive cross-sectional design. The population and sample of this research are Indonesian language teachers in West Bandung Indonesia. Data was taken for 1 month starting on March 14, 22 to April 18, 2022. The data collection technique used questionnaire that has been tested for validity and reliability then the questionnaire distributed through google form. Data processing techniques used excel and SPSS 24 then interpreted by using the Guuttman scale. The results that 1) portrait of Indonesian language teacher's digital literacy on AKM kelas and Asesmenpedia is strong enough with a value of 0.61. 2) the level of understanding of the Indonesian language teacher on the AKM Class Application and Asesmenpedia with a value of 0.61 it was strong enough criteria. 3) there is a perfect relationship between the digital literacy ability of the Indonesian language teacher with AKM kelas and Asesmenpedia. The result of Correlation Person value showed that points 0.923.